The Structural and Stress Analysis of Hemrin North Structure, North of Iraq. - Al-baldawi, Buraq A. H.; AL-Hachem, Atheer E.K. (Journal of Petroleum Research and Studies, 2022)
The study focused on the results of first paleostress from thrust fault slip data on Tertiary age of Hemrin North Structure, North of Iraq. The stress inversion was performed for fault slip data using an improved right dihedral model, and then followed by rotational optimization (Georient Software). The trend of the principal stress axes (σ1, σ2 and σ3) and the ratio of the principal stress differences (R) show the main paleostress field is NE-SW compression regime. As well as using Lisle graph and Mohr diagram to determine the magnitudes of palestress. The values paleostress of the study area were σ1=1430 bars, σ2=632 bars and σ3=166 bar. The large magnitudes of the primary stress axes could be attributed to active tectonic processes that caused pre-Tertiary deformation.